La estructura de los costos y su incidencia en la rentabilidad de la Compañía Fábrica de Productos Químicos Santa Elena FABPROQUIM CÍA. LTDA. - Chapa Rivadeneira, Christopher Steeve (2023)
The following research work focuses on analyzing how a company distributes its costs and on understanding how different cost elements can affect the profitability of a company. A study of the relationship between the cost structure, the distribution of fixed costs and variable costs affects the profit margins of the company will be carried out. The impact that the cost structure has on the profitability of the company subject to analysis will be explored and how their efficient management can improve profitability and long-term business success, as well as determining how internal processes can be improved to reduce these costs and increase profitability. Spreadsheets will be used as the main resource, in addition to analyzes to evaluate costs in different areas of the company and solutions will be proposed to improve efficiency and reduce costs in order to provide practical recommendations to help the company improve its profitability. through cost management. Proper cost management is essential to improve the profitability of a company; This is achieved by identifying and analyzing internal processes that significantly contribute to costs, proposing their optimization and finding solutions to improve efficiency. The thesis will defend that cost management is a fundamental tool for effective financial management and business decision making.